Cognitive stimulation and dementia: traditional interventions vs. computer-based methodologies - Mendes,Liliana (2024)
ABSTRACT We aim to examine the role of cognitive stimulation interventions applied to healthy older adults or older adults with mild-to-moderate dementia. The most important benefits and differences between using these programs without computerized tasks compared to computer-based assistive technologies are also addressed. We conducted a literature review which includes empirical studies in the cognitive stimulation field, applied to healthy older adults or in participants with some type of dementia. All studies include cognitive stimulation intervention using traditional methods or computer-based assistive technology. We included a total of 35 studies in our review. In general, our findings provide support for applying cognitive stimulation programs, using traditional methods or computer-based assistive technology, specifically for older people with dementia. However, we found heterogeneity regarding methods, design of intervention, and procedures in both types of methodology. This review adds value towards a systematisation of heterogeneous data existing in this field. However, it remains difficult to perform unbiased comparisons. Future studies should provide a comparative assessment of the effectiveness of cognitive stimulation programs using computer-based assistive technology involving older adults at various stages of dementia, as well as the efficacy and reliability of this type of intervention, practical effects and the potential to delay or prevent dementia.